Cranial internal hemipelvectomy (iliectomy) with limb sparing for a dog with ilial chondrosarcoma: A case report. Issue 1 (11th January 2022) - Downey, Amy C.; Mathews, Kyle G.; Borst, Luke
Abstract: Cranial internal hemipelvectomy can be successful for excision of ilial CSA with minimal complications. Iliectomy with adjuvant radiation therapy was well tolerated in a dog with grade II ilial CSA. The dog survived 1, 271 days postoperatively and supposedly succumbed to a disease process unrelated to the CSA. Abstract : Cranial internal hemipelvectomy can be successful for excision of ilial chondrosarcoma in dogs, with minimal complications. Iliectomy was well tolerated and resulted in good hindlimb function postoperatively.